2008
DOI: 10.1007/s11947-008-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep Frying Performance of Enzymatically Synthesized Palm-Based Medium- and Long-Chain Triacylglycerols (MLCT) Oil Blends

Abstract: The main aim of this work was to assess the frying strength of the enzymatically synthesized palmbased medium-and long-chain triacylglycerols (MLCT) oil with the aid of different antioxidants under deep-frying conditions. Palm-based MLCT oil in the presence of synthetic or natural antioxidants showed significantly better (P<0.05) thermal resistance and oxidative strength than refined, bleached, and deodorized (RBD) palm olein throughout the five consecutive days of frying. Rancimat induction period, free fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…It is well known that lipid quality in foods is significantly influenced by its oxidative status (Koh et al 2008). Thus, the undoubtedly positive health benefits associated with the lipid composition achieved in the modified products might involve a higher risk for the oxidative stability of the developed product.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that lipid quality in foods is significantly influenced by its oxidative status (Koh et al 2008). Thus, the undoubtedly positive health benefits associated with the lipid composition achieved in the modified products might involve a higher risk for the oxidative stability of the developed product.…”
Section: Resultsmentioning
confidence: 99%
“…However, K 232 and K 268 showed small increments in the last two days, which was related to the equilibrium that was established between the rate of formation of conjugated dienes and carbonyl compounds and the rate at which these compounds were transformed into oligomers and polymers (Abdulkarim et al, 2007;Koh et al, 2011).…”
Section: Specific Extinction Coefficientsmentioning
confidence: 98%
“…Table 4 shows fat content of fried chicken chops as a function of frying method and time. In previously published studies (Koh et al, 2011;Debnath et al, 2012;Mishra & Sharma, 2014), it was noted that the frying time had remarkable influence on oil content of fried products. This was also observed in the present study, where oil content showed significant (p<0.05) increment in the last day and in the last three days in the case of DWF and PDF, respectively.…”
Section: Cie Color Valuesmentioning
confidence: 98%
“…They found that fatty acids in these oils have great influence on the physical and chemical properties of the product. The frying quality of enzymatically synthesized palm oil based medium and long-chain triacylglycerols in presence of synthetic or natural antioxidants were evaluated under deep-frying conditions by Koh et al (2011). They observed that the presence of antioxidants showed significantly better thermal resistance and oxidative strength as compared to its control oil.…”
Section: Introductionmentioning
confidence: 99%